2006
DOI: 10.1007/s11262-006-0056-x
|View full text |Cite
|
Sign up to set email alerts
|

The spreading of HIV-1 infection in the human organism is caused by fractalkine trafficking of the infected lymphocytes—a review, hypothesis and implications for treatment

Abstract: The reviews on HIV-1/AIDS [1-8] highlighted the mechanism by which HIV-1 virions utilize dendritic cells (DCs) for transport from the genitals, the portal of virus infection, to the draining lymph nodes where DCs carry HIV-1 virions and present viral antigens by HLA class I and II to CD4(+) T cells. Interaction of the T cells with viral antigens presented by HLA class II molecules polarizes them to become Th2 cells, the targets of HIV-1 infection and producers of HIV-1 progeny virions. The T cells which intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…It had been suggested that fractalkine trafficking of HIV-infected lymphocytes propagates the dissemination of HIV in vivo. 26 Of the 30 cytokines that we evaluated, only fractalkine was associated with viral load, and this association remained significant after adjusting for CD4 count. Similarly, Widney et al found that CXCL13-a B cell stimulatory chemokines-is elevated in HIV infection and correlated with CD4 count and HIV viral load.…”
mentioning
confidence: 82%
“…It had been suggested that fractalkine trafficking of HIV-infected lymphocytes propagates the dissemination of HIV in vivo. 26 Of the 30 cytokines that we evaluated, only fractalkine was associated with viral load, and this association remained significant after adjusting for CD4 count. Similarly, Widney et al found that CXCL13-a B cell stimulatory chemokines-is elevated in HIV infection and correlated with CD4 count and HIV viral load.…”
mentioning
confidence: 82%
“…Functionally, fractalkine is highly pleiotropic [23,27], acting as both an adhesion molecule and chemoattractant for T cells, NK cells, and macrophages [24,29,30]. CX 3 CR1 can also serve as an HIV-1 co-receptor with CD4 [31-33] and is hypothesized to facilitate the spread of HIV-1 infection [34]. Within the nervous system, fractalkine serves a major role as a membrane-tethered neuronal chemokine, while the Cx3cr1 gene is highly expressed by microglia [26,35].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, other investigators report reductions in fractalkine and CX 3 CR1 levels and signaling in neuroAIDS [45]. More recently, fractalkine has been proposed as important for trafficking HIV-infected lymphocytes into the brain [34,42]. Soluble fractalkine attenuates gp120 toxicity in hippocampal neuron cultures in the presence or absence of a glial feeder layer suggesting a direct neuroprotective role [46].…”
Section: Introductionmentioning
confidence: 99%
“…CCL2, which is up-regulated in activated microglia and constitutively produced by neurons [97], plays a central role in HAND by attracting microglia [98] and monocytes [99-101] into the central nervous system and is considered a marker of poor prognosis [102-105]. CX3CL1 and its receptor CX3CR1 have received increased attention regarding their roles in HIV-1 infection [106-108] and in HAND specifically [106,109,110]. CX3CL1 is expressed by neurons and astrocytes [111], where it induces microglial proliferation [111] and migration [112].…”
Section: Discussionmentioning
confidence: 99%